1990
DOI: 10.1177/00220345900690021301
|View full text |Cite
|
Sign up to set email alerts
|

Colonization Resistance of Defined Bacterial Plaques to Streptococcus mutans Implantation on Teeth in a Model Mouth

Abstract: We investigated the ability of Streptococcus mutans C67-1 to colonize simple bacterial plaques and the effects of age and stability of the pre-formed plaque on colonization resistance. Mixed-plaques of Actinomyces viscosus WVU627, 'Streptococcus mitior' LPA-1, and Veillonella dispar OMZ193 were grown on tooth segments, mounted back to back for simulation of approximal sites in a model mouth for 66 h. S. mutans C67-1 was either included in the original inoculum or super-inoculated onto the developing plaque. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Laboratory strains of human origin were used, as described pre viously [Perrons and Donoghue, 1990]. Actinomyces viscosus WVU 027 is a serotype 2 strain.…”
Section: Icroorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory strains of human origin were used, as described pre viously [Perrons and Donoghue, 1990]. Actinomyces viscosus WVU 027 is a serotype 2 strain.…”
Section: Icroorganismsmentioning
confidence: 99%
“…S. oralis and V. dispar. In subsequent 66-hour experiments, S. mutans was superinoculated onto the developing plaque after 24 h, when colon ization resistance has developed [Perrons and Donoghue, 1990]. To distinguish the effect of incubation time from colonization resist ance, S. mutans was grown in pure culture in the model mouth for the equivalent incubation time of 42 h.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbiological monitoring following chlorhexidine varnish treatment sug gested that this long-term suppression of mutans strepto cocci is mainly due to bacterial interference [Schaeken et al, 1989]. Earlier studies indicated that streptococci from the Streptococcus oralis group, such as Streptococcus gordonii, S. oralis, Streptococcus sanguis and Streptococcus mitis, and Actinomyces species play a role in the suppres sion of mutans streptococci [Mikx et al, 1975; van der Hoe ven and Rogers, 1979;McDermid et al, 1987;Perrons and Donoghue, 1990], Indeed, using gnotobiotic rats it could be demonstrated that Streptococcus and Actinomyces strains inhibit regrowth of Streptococcus mutans after chlorhexi dine application [van der Hoeven and Schaeken, 1995], It is not surprising that physiologically related bacteria are in volved in control of mutans streptococci in dental plaque. However, it is not known how specific the relationship is, and if particular Streptococcus and Actinomyces species have more effect than others in controlling mutans strepto- …”
mentioning
confidence: 99%
“…We have earlier ascribed the long-term suppression of mutans streptococci after stop of chemotherapy to bacterial interfe rence. Their growth after chemotherapy seemed to be inhib ited by other microorganisms in dental plaque, and partic ularly by other streptococci and actinomyces [Schaeken et al, 1989], This hypothesis stems from observations that ex perimental colonization of sites of the dentition by mutans streptococci is often difficult, and spread of the organisms throughout the mouth is limited [Mikx et ah, 1975;Loesche, 1977, 1978;van der Hoeven and Rogers, 1979], Further support for microbiological control of Strep-tococcus mutans populations in ecosystems comes from mixed-culture chemostat studies and artificial mouth mod els [McDermid et al, 1989;Perrons and Donoghue, 1990],…”
mentioning
confidence: 99%